تمثلات الدروس الخصوصية لدى الأسرة الجزائرية - بن فارح، نبيلة; تريكي، أحمد Triki, Ahmed (جامعة العربي التبسي تبسة - مخبر الدراسات الإنسانية والأدبية, 2023)
يهدف هذا البحث إلى الكشف عن مدى اتجاه الأسر الجزائرية نحو الدروس الخصوصية ومعرفة تمثلات الأسر لهذه الظاهرة إيجابية، سلبية، أم محايدة، وباستخدام المنهج الوصفي لتحديد ووصف هذه التصورات، تمت الاستعانة بأداة الاستمارة كأداة أساسية في هذه الدراسة وبتطبيقها على العينة القصدية تمثلت في أولياء الأمور، وبلغ عدد المبحوثين 130 مبحوث، وقد تم التوصل إلى النتائج التالية: أن الدروس الخصوصية ظاهرة مرحب بها في أواسط الأسر الجزائرية، وما هي إلا قرار يتم اتخاذه للرفع بالمستوى التعليمي، وفي ضوء هذه النتائج تقترح الدراسة تنصيص عقوبات صارمة على منشئي أقسام الدروس الخصوصية بطرق غير قانونية، والتكوين الجيد والمتميز للأساتذة من أجل تحقيق الأهداف المتطلبة دون اللجوء إلى الدروس الخصوصية. The aim of This research is to reveal the extent to which Algerian families tend towards private lessons, and to know Representation of families towards this phenomenon, positive, negative, or neutral, and by using the descriptive approach to identify and describe these perceptions. The questionnaire was used as a basic tool in this study and was applied to the intended sample of parents, and the number of respondents reached 130, and the following results were reached: that private lessons are a welcome phenomenon among Algerian families, It is only a decision to be taken to raise the educational level. In light of these results, the study proposes stipulating strict penalties for the creators of private tutoring departments through illegal methods, and good and distinguished training for the teachers in order to achieve the required goals without resorting to private lessons.
Keywords: الدروس الخصوصية -- الأسر الجزائرية -- المستويات التعليمية